2013
DOI: 10.4028/www.scientific.net/kem.594-595.427
|View full text |Cite
|
Sign up to set email alerts
|

Fire Resistance Evaluation of Lightweight Geopolymer Concrete System Exposed to Elevated Temperatures of 100-800 °C

Abstract: This paper reports the fire resistance property of a lightweight aggregate geopolymer concrete (LWAGC) material synthesized by the alkali-activation of locally source fly ash (FA) after exposed to elevated temperatures ranged of 100 °C to 800 °C. The results illustrates that the concrete gained a compressive strength after exposing to elevated temperatures of 100, 200 and 300 °C. Afterward, the strength of the LWAGC is started to deteriorate after exposing to elevated temperatures ranged of 400 °C to 800 °C, d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 11 publications
(16 reference statements)
0
4
0
Order By: Relevance
“…This thermal exposure induces the processes of dehydration and de-hydroxylation within the Geo-Polymer gel, resulting in a discernible loss of both mass and bulk density in the concrete. In their comprehensive study, Abdulkareem et al [109] meticulously examined the behavior of hardened Geo-Polymer materials under these conditions and identified three distinct forms of water trapped within the material that can escape during heating. Vapor pressure continues to rise above 100℃, resulting in mass loss when water adsorbed to the binder's surface is removed between room temperature and 100℃, and when pore water is eliminated between 100℃ and 1000℃.…”
Section: Volume Stability and Mass Lossmentioning
confidence: 99%
“…This thermal exposure induces the processes of dehydration and de-hydroxylation within the Geo-Polymer gel, resulting in a discernible loss of both mass and bulk density in the concrete. In their comprehensive study, Abdulkareem et al [109] meticulously examined the behavior of hardened Geo-Polymer materials under these conditions and identified three distinct forms of water trapped within the material that can escape during heating. Vapor pressure continues to rise above 100℃, resulting in mass loss when water adsorbed to the binder's surface is removed between room temperature and 100℃, and when pore water is eliminated between 100℃ and 1000℃.…”
Section: Volume Stability and Mass Lossmentioning
confidence: 99%
“…Another important benefit of geopolymer cement is its resistance to acid and sulphate attack (Glasby et al, 2014), as well as freeze-thaw cycles (Abdulkareem et al, 2014). In terms of sulphate resistance, results from Douglas et al (1992) indicate that changes in the mechanical properties of geopolymer cement concrete specimens were minimal, after 120 days immersion in a 5% sodium sulphate solution.…”
Section: Other Propertiesmentioning
confidence: 99%
“…Further research has also indicated good resistance to acids, such as sulphuric acid and hydrogen chloride (Ariffin et al, 2013;Shi, 2003;Banah UK, 2014). In addition, Provis & van Deventer (2009), Davidovits (2013) and Abdulkareem et al (2014) discussed freeze-thaw properties. Mass loss of less than 0.1% and strength loss of 5% after 180 cycles was recorded by the Geopolymer Institute (2008).…”
Section: Other Propertiesmentioning
confidence: 99%
“…The effect of LECA on the efficiency of GGBS-based concrete was investigated by Yang et al 15 The specimens were cured at room temperatures and compressive strength obtained for 28 days ranged from 3.3 to 19.1 MPa with a density of 775-1615 kg/ m 3 . Abdulkareem et al 16 investigated the influences of temperatures on the mechanical characteristics of lightweight geopolymer concrete (LWGC). They manufactured lightweight geopolymer concrete with fly ash as raw material, LECA as coarse aggregate, and normal sand as fine aggregate.…”
Section: Introductionmentioning
confidence: 99%